Hyperglycaemia, oxidative stress and inflammatory markers - Butkowski, Eugene G. (Redox Rep, 2016)
Introduction: The increasing prevalence of hyperglycaemia implicates a state of oxidative stress and inflammation. Traditional and emerging biomarkers associated with increasing hyperglycaemia were assessed to clarify their role they play in hyperglycaemia. Results: 309 participants attending a rural diabetic screening program were categorised into control and quintile groups based upon glucose levels: 1st quintile - <4.5 mmol/L and 4th, 5th quintile - >6.1 mmol/L. Significant results were obtained for anthropometric data and biochemical markers - glucose, HbA1c and total cholesterol (P < 0.001); oxidative stress: glutathione (P < 0.001), glutathione:glutathione disulfide and 8-hydroxy-2-deoxyguanosine (P < 0.05). Interleukin -1β and inflammatory marker ratios IL-6/IL-10, IL-1β/IL-10, MCP-1/IL-10, IGF-1/IL-10 and IL-6/IL-1β were significant (P < 0.05). Conclusion: This study provided further evidence that inflammatory and oxidative stress biomarkers may contribute to diagnostic information associated with preclinical increases in BGL. Further we have provided a unique study in the analysis of ratios of inflammatory biomarkers and correlations with increasing BGL.